2002
DOI: 10.1074/jbc.m200061200
|View full text |Cite
|
Sign up to set email alerts
|

Rac Activation Induces NADPH Oxidase Activity in Transgenic COS Cells, and the Level of Superoxide Production Is Exchange Factor-dependent

Abstract: . Rac effector domain point substitutions (A27K, G30S, D38A, Y40C), which can selectively eliminate interaction with different effector proteins, impaired Rac1V12-induced superoxide production. Activation of endogenous Rac1 by expression of constitutively active Rac-guanine nucleotide exchange factor (GEF) derivatives was sufficient to induce high level NADPH oxidase activity in COS phox cells. The constitutively active form of the hematopoieticspecific GEF, Vav1, was the most effective at activating superoxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
99
1
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(112 citation statements)
references
References 76 publications
9
99
1
3
Order By: Relevance
“…Such cells expressed normal levels of MEF2C, featured regular sarcomeres, and thus differentiated normally into functional beating cardiac cells. Furthermore, day-to-day addition of 100 nM H 2 O 2 at early stage of differentiation (days 0 -7), at a concentration expected from RacV12 activity within differentiating cells (Price et al, 2002), to the EBs also severely impaired cardiac differentiation of ES cells, as shown by the lack of both transactivation of the MEF2C-dependent ␣-actin promoter and beating activity of EBs. On the other hand, the ROS scavenger, catalase added to the culture medium of EBs rescued MEF2C expression, myofibrillogenesis and in turn beating activity of RacV12 EBs.…”
Section: Discussionmentioning
confidence: 99%
“…Such cells expressed normal levels of MEF2C, featured regular sarcomeres, and thus differentiated normally into functional beating cardiac cells. Furthermore, day-to-day addition of 100 nM H 2 O 2 at early stage of differentiation (days 0 -7), at a concentration expected from RacV12 activity within differentiating cells (Price et al, 2002), to the EBs also severely impaired cardiac differentiation of ES cells, as shown by the lack of both transactivation of the MEF2C-dependent ␣-actin promoter and beating activity of EBs. On the other hand, the ROS scavenger, catalase added to the culture medium of EBs rescued MEF2C expression, myofibrillogenesis and in turn beating activity of RacV12 EBs.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins that regulate membrane fusion or fission include dynamin 2 [39], amphiphysin IIm [40], Arf6 [41,42], Rab5 [43,44], Rab11 [45], and PLA 2 [46]. Proteins that may affect the assembly and activation of the NADPH oxidase complex include Rac1, Rac2 [10], Vav1 [47], PAK1 [48], protein kinase C (PKC)␣ and PKCε [49,50], myristoylated alanine-rich C kinase substrate [49], and Akt [51]. Libraries of monoclonal antibodies and proteomic analyses have indicated that many more proteins, named or unnamed, are present on phagosomes [24,33].…”
Section: Proteins Downstream Of the Fcr Complexmentioning
confidence: 99%
“…Esta línea celular había sido transfectada previamente de manera estable con los cADN de gp91 phox , p22 phox y p47 phox clonados en los vectores pEF-PGKpac, pEF-PGKneo y pEF-PGKhygro, respectivamente (40)(41)(42). Estas células se cultivaron en medio DMEM/10% suero bovino fetal (SBF) (Hyclone, Logan, UT) con suplemento de 50 unidades/ml de penicilina, 50 µg/ml de estreptomicina (Gibco BRLÒ Life Technologies), 0,2 mg/ml de higromicina (Invitrogen), 1,8 mg/ml de G418 y 1 µg/ml de puromicina (Sigma-Aldrich, St. Louis, MO).…”
Section: Transfección De La Línea Celular Cos91/22/47unclassified
“…Se mezclaron 3 x 10 6 células COS91/22/47 con 2 µg de los respectivos cADN clonados en pcADN3.1/zeo(+). Éstas se analizaron 21 horas después de la transfección como se menciona en los ensayos de Price et al (41,42).…”
Section: Transfección De La Línea Celular Cos91/22/47unclassified
See 1 more Smart Citation